Analisa Perputaran Piutang Usaha Terhadap Efektivitas Arus Kas: Studi kasus Pada Perusahaan Distributor ABC di Surabaya - Tjandra Wasesa (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
Planning efforts as well as receivable turnover analysis are needed to determine management policies. Management of receivable procedures, credit sales, and collection of receivables to the write-off of trade receivables is expected to run effectively. Accounts receivable turnover is directly related to cash flow, so it will affect the company's operational activities. This study intends to describe the analysis of accounts receivable turnover on the effectiveness of cash flow in distributor companies in Surabaya. More or less trade receivables will affect the effectiveness of cash flow, because more and more money capital is stuck on uncollectible receivables, it will hamper the smooth operation of operations that depend on cash flow turnover. In the results of this study it was found that the results of the application of receivables turnover analysis showed an increasing improvement, although the average period of collection of receivables was still relatively slow, but this became an evaluation as well as input for the company to take a plan in providing sales on credit in the future. come.